2010
DOI: 10.1002/ejoc.201000427
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Carbenoid Rearrangement of 2‐Phenyl Substituted gem‐Dihalogenospiropentanes

Abstract: The series of 2-phenyl-and 2,2-diphenyl gem-dihalogenospiropentanes were employed as model compounds to study the carbenoid rearrangement with the use of methyllithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Bromofluorospiropentane on treatment with MeLi gave a tricyclic system exclusively (Scheme 58). 24 At the same time the reaction between MeLi and bromochlorospiropentane gave exclusively the hexacyclic dimeric product. If the dibromo compound was subjected to the reaction, a mixture of tricyclic and dimerized products was obtained.…”
Section: Rearrangementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bromofluorospiropentane on treatment with MeLi gave a tricyclic system exclusively (Scheme 58). 24 At the same time the reaction between MeLi and bromochlorospiropentane gave exclusively the hexacyclic dimeric product. If the dibromo compound was subjected to the reaction, a mixture of tricyclic and dimerized products was obtained.…”
Section: Rearrangementsmentioning
confidence: 99%
“…Sometimes the dihalocyclopropane derivatives are essential as reactive intermediates for the synthesis of naturally occurring compounds. 24 Here, dibenzo-18-crown-6 was used as the phase transfer catalyst for the generation of bromofluorospiropentane, TEBAC for bromochlorocyclopropane and KO t Bu for dibromocyclopropane derivatives, respectively. In the preparation of (±) grenadamide, use of dibromocarbene for cyclopropanation under phase transfer catalysis was employed (Scheme 12).…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclomentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy to the synthesis of dichlorocyclopropanes, Averina et al reported the addition of bromofluorocarbene to olefins to synthesize gem-bromofluorocyclopropanes. 12 In their early report, the authors reported the use of a bi-…”
Section: Addition Of Fluorocarbenes To Alkenesmentioning
confidence: 99%